Previous use of angiotensin-II receptor blockers in hospitalized hypertensive patients and COVID-19 mortality - Oscanoa, Teodoro J. (2022)
Introduction: There is currently great interest in establishing the relationship between the severity of SARSCOV-2 infection in hypertensive patients who use angiotensin II antagonists (AIIRAs). Objective: To study the relationship between the previous use of angiotensin II antagonists (ARB) in hypertensive patients and mortality from COVID-19. Materials and methods: A retrospective observational study was carried out in a tertiary care hospital in Lima, Peru, in hypertensive patients hospitalized in March 2021 for severe COVID-19. Results: A total of 101 patients entered the study, with a mean age of 70.1 + 12.0 and 48% male. ARB users and non-users were 45 (45.6%) and 56 (54.4%), respectively. The Charlson Comorbidity Index was higher in the ARB group (3.6 + 1.56 vs 3.04 + 1.24) (p<0.05). Total and male vs women mortality, among those using ARBs or not, were 57.8% vs 62% (p = 0.633) and 36.36% vs 63.64% (p <0.05), respectively. Mean lactate dehydrogenase concentration was lower in those taking ARBs compared to non-users, 394.18 + 152.3 vs 503.5 + 252.7 (p<0.05); No significant difference was observed in the leukocyte count and serum levels of C-Reactive Protein, Ferritin, D-dimer and fibrinogen. Conclusion: Among hospitalized COVID-19 patients with hypertension, prior use of ARBSs was not associated with mortality risk.